2010
DOI: 10.1002/mats.201000047
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening Transition in Semiflexible Cyclic Macromolecules

Abstract: Conformational changes in cyclic and linear chains triggered by increasing chain stiffness are explored using MC simulations. The transition to the rigid strained objects is continuous and steeper for cycles. Circular macromolecules of contour length equal to ≈5 persistence lengths are characterized as rigid strained objects with a lowered spatial dimensionality. The coil regime is almost omitted in the static structure factor already for semiflexible chains of both architectures and the flattening of stiffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…For this root we also have t 1 = cos(2π/N), which corresponds to an angle of 2π/N between neighboring bonds of a regular polygon of N sides. We note that envisaging a planar rigid polygonal structure as limiting case is also in line with recent simulation results on semiflexible rings, 18,19 in which with growing stiffness a flattening of the rings to a quite planar shape was observed.…”
Section: A the Limiting Case T → X −supporting
confidence: 87%
“…For this root we also have t 1 = cos(2π/N), which corresponds to an angle of 2π/N between neighboring bonds of a regular polygon of N sides. We note that envisaging a planar rigid polygonal structure as limiting case is also in line with recent simulation results on semiflexible rings, 18,19 in which with growing stiffness a flattening of the rings to a quite planar shape was observed.…”
Section: A the Limiting Case T → X −supporting
confidence: 87%
“…Abreu and Escobedo obtained using a configurational‐bias Monte Carlo method for polymers in the good solvent condition a value of g = 0.62 for the ring‐shaped case and g = 0.46 for the theta‐shaped case. However, those values may not be conclusive because their value of g = 0.62 for ring‐shaped polymers was larger than those usually reported by others . Uehara et al studied the radius of gyration of caged polymers without excluded volume interactions by a quaternionic method for generating random polygons and random walks, and they found that the ratio of 〈 S 2 〉( f , N )/〈 S 2 〉( f = 2, N ) increases monotonically with respect to the number of bridges f , and approaches a constant value of about 1.3 for large f .…”
Section: Introductionmentioning
confidence: 93%
“…At the present time, there is no general agreement on the value of g for ring‐shaped polymers in good solvent. There have been extensive studies on this issue by theory, experiments, and computer simulations in the literature . Most reported values fell in the range of 0.52–0.62, all larger than the ideal chain value of 0.5.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations